2017
DOI: 10.1186/s12883-017-0932-0
|View full text |Cite
|
Sign up to set email alerts
|

Association between multiple sclerosis, cancer risk, and immunosuppressant treatment: a cohort study

Abstract: BackgroundThe association between multiple sclerosis (MS) and cancer has long been investigated with conflicting results. Several reports suggest an increased cancer risk among MS patients treated with immunosuppressant (IS) drugs.MethodsWe performed a cohort study including MS patients recruited at the Neurological Department of the University of Palermo. Mean follow-up period was ten years for the whole cohort. We calculated cancer incidence among patients treated with IS. Incidence rates were compared in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 23 publications
2
36
0
Order By: Relevance
“…As described, comorbidities in PwMS can impact on DMT adherence and, therefore, and may influence the choice of DMT [3,112],however, this report suggests that DMT use may also increase the risk of developing comorbidity across several conditions in PwMS. For example, interferon beta and glatiramer acetate uses have been associated with an increased prevalence of cardiovascular risk factors, including elevated diastolic blood pressure and plasma glucose, in addition to altered lipid profiles [29],other studies have suggested that DMT use may increase cancer risk in PwMS [94][95][96]. Therefore, improved understanding of the effects of comorbidity on safety, the effectiveness of DMT, and potential interactions between DMT use and comorbidity in PwMS is needed.…”
Section: Dmt Use May Interact With the Comorbid Disease In Pwmsmentioning
confidence: 99%
“…As described, comorbidities in PwMS can impact on DMT adherence and, therefore, and may influence the choice of DMT [3,112],however, this report suggests that DMT use may also increase the risk of developing comorbidity across several conditions in PwMS. For example, interferon beta and glatiramer acetate uses have been associated with an increased prevalence of cardiovascular risk factors, including elevated diastolic blood pressure and plasma glucose, in addition to altered lipid profiles [29],other studies have suggested that DMT use may increase cancer risk in PwMS [94][95][96]. Therefore, improved understanding of the effects of comorbidity on safety, the effectiveness of DMT, and potential interactions between DMT use and comorbidity in PwMS is needed.…”
Section: Dmt Use May Interact With the Comorbid Disease In Pwmsmentioning
confidence: 99%
“…Several studies have found that while cancer risk in MS patients may not differ from the general population, the risk appears to be lower in male patients compared to female patients, and increases with age (7,14,15). Overall, there is general agreement that immunosuppressant therapies, such as azathioprine, methotrexate, cyclophosphamide, and mitoxantrone have led to increased cancer risks in MS patients and this risk is related to patient's family history of cancer, duration of treatment and cumulative dose (16,17). More recent large cohort studies, have incorporated oral and IV therapies along with other cancer risk factors, such as alcohol and smoking, demonstrating no increase in cancer risk in MS population (7,18,19).…”
Section: Introductionmentioning
confidence: 99%
“…Continuous immunosuppression has important functional consequences for the therapeutic use of these drugs, as this treatment has been associated with an increased risk of infections [12,13] and, in some cases, increased risk of malignancy [14,15]. The implications of these observations for individual DMDs, including those that act like IRTs, is described in the following sections.…”
Section: Immunomodulation Versus Immunosuppressionmentioning
confidence: 99%